Discourse, identity and the question of Turkish accession to the EU through the looking glass - Macmillan, Catherine (Ashgate Pub., 2013)
The focus on elite discourse provides a new and engaging approach to this contentious topic and offers a unique understanding of the competing arguments within the EU regarding the question of Turkey's accession and the differing visions for the European Union that underlie them.